Maternal perspectives on infant feeding practices in Soweto, South Africa. Issue 12 (10th August 2021) - Wrottesley, Stephanie V; Prioreschi, Alessandra; Slemming, Wiedaad; Cohen, Emmanuel; Dennis, Cindy-Lee; Norris, Shane A
Abstract: Objective: To (i) describe the infant feeding practices of South African women living in Soweto and (ii) understand from the mothers' perspective what influences feeding practices. Design: Semi-structured focus group discussions (FGD) and in-depth interviews (IDI) were conducted, and data were analysed using thematic analysis. Setting: Soweto, South Africa. Participants: Nineteen mothers were stratified into three FGD according to their baby's age as follows: 0–6-month-olds, 7–14-month-olds and 15–24-month-olds. Four mothers from each FGD then attended an IDI. Results: Although mothers understood that breast-feeding was beneficial, they reported short durations of exclusive breast-feeding. The diversity and quality of weaning foods were low, and 'junk' food items were commonly given. Infants were fed using bottles or spoons and feeding commonly occurred separately to family meal times. Feeding practices were influenced by mothers' beliefs that what babies eat is important for their health and that an unwillingness to eat is a sign of ill health. As such, mothers often force-fed their babies. In addition, mothers believed that feeding solid food to babies before 6 months of age was necessary. Family matriarchs were highly influential to mothers' feeding practices; however, their advice often contradicted that of health professionals. Conclusions: In South Africa, interventions aimed at establishing healthier appetites and eating behaviours in early life should focus on: (i) fostering maternal self-efficacy around exclusive breast-feeding; (ii) challenging mixed feeding practices and encouraging more responsive feeding approaches and (iii) engaging family members to promote supportive household and community structures around infant feeding.